Physicochemical and Mechanical Characterization of Meloxicam-Fumaric Acid Co-Crystals Synthesized by Ultrasound-Assisted Solution Method - Hestiary Ratih; Jessie Sofia Pamudji; Fikri Alatas; Viska Elvira Alawiyani; Nur Achsan Al-Hakim (Jurnal Kimia Sains dan Aplikasi, 2026)
Meloxicam (MLX) is a class II BCS non-steroidal anti-inflammatory drug (NSAID) with low solubility and manufacturing challenges due to its needle-like crystal habit, which causes poor flowability and high elasticity. These mechanical characteristics often trigger capping and lamination during direct compression. This study aims to perform physicochemical characterization and mechanical property evaluation of MLX co-crystals with fumaric acid (FUM) co-former, synthesized using the ultrasound-assisted solution co-crystallization (USSC) method. The co-crystals were synthesized at a 1:1 molar ratio in ethanol solvent using ultrasonication. Characterization was performed using a polarizing microscope, PXRD, DSC, and FTIR, followed by evaluation of flow properties, compressibility, and tabletability. The results of PXRD, DSC, and FTIR analyses confirmed the formation of a new co-crystal phase via intermolecular hydrogen-bonding interactions. A morphological transformation was observed from a needle habit to a more isodiametric or plate-like habit. The MLX-FUM co-crystal showed significant improvements in flow rate (0.134 g/sec), angle of repose (33.86°), and compressibility index (38.92%) compared to pure MLX. Tabletability analysis showed a fivefold increase in tensile strength (2.70 MPa) at a pressure of approximately 2.94 MPa (30 kg/cm2), which correlated with a decrease in elastic recovery from 3.18% to 1.96%. This study concludes that co-crystal synthesis by USSC holistically improves the mechanical profile of MLX, showing an improved mechanical profile that demonstrates potential for tablet manufacturing processes using the direct compression method.